Paving the Way to Sustained Growth and Prosperity in Central America, Panama, and the Dominican Republic - Beaton, Kimberly (International Monetary Fund, 2019)
Abstract: Accelerating economic growth in Central America, Panama and the Dominican Republic (CAPDR) remains an elusive task. While the region performed relatively well in the post-global financial crisis period, over the last five years obstacles to growth have become more evident and new challenges have emerged. In response, the region has strengthened macro-financial frameworks but more progress will be required to pave the way to sustained growth and prosperity. This book considers the structural factors underlying the region's growth outlook and assesses its macroeconomic and financial challenges to help shape the policy agenda going forward. The book first identifies the structural determinants of growth in the region related to: capital formation; employment; demographic factors, including immigration; productivity; and violence. It then highlights the importance of creating fiscal space through the design and implementation of fiscal rules and mechanisms to increase accountability (better quality of public spending, adequate policies to reduce income inequality and sustainable retirement plans). Finally, it presents recent evidence on the importance of a supportive financial sector for growth (including through financial inclusion and development).